Optimizing English vocabulary acquisition through music-based learning methods: Pedagogical strategies and measurable learning outcomes - Ni Putu Meisya Divania Putri; Ratri Paramita; Muhammad Zulfan (Yayasan Mitra Persada Nusantara, 2026)
This study aims to evaluate the effectiveness of music-based learning in enhancing English vocabulary acquisition among learners. A mixed-method approach was employed, involving experimental interventions where participants engaged with English songs through activities such as guided listening, lyric analysis, and singing. Pre- and post-tests measured vocabulary retention and acquisition, while qualitative feedback assessed learner motivation and attitudes. Data analysis revealed significant improvements in vocabulary scores, with music-based methods outperforming traditional instruction in both short- and long-term retention. Additionally, learners reported increased engagement, reduced anxiety, and greater enjoyment during the learning process. The findings support integrating music as a dynamic pedagogical tool to foster vocabulary growth and positive language learning experiences.